Low family support perception: a 'social marker' of substance dependence? - Lemos, Valdir de Aquino [UNIFESP] (2012)
OBJECTIVE: Simultaneously assess the relationship between the family support perception and the intensity of hopelessness, depression, and anxiety symptoms in alcohol or drug dependent (AOD) patients and in non-AOD dependent control group (CON). METHOD: 60 patients who met the DSM-IV criteria for AOD dependence and 65 individuals with similar profile, but not dependent on AOD completed the Family Support Perception Inventory (FSPI), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Beck Hopelessness Scale (BHS). RESULTS: Logistic regression analysis indicated that high scores in family autonomy (OR = 0.08), and low scores in hopelessness (OR = 0.64) were negatively correlated with AOD dependence. Individuals with high scores in BAI had higher probability (OR = 1.22) of belonging to the AOD group, as well as those who reported previous psychiatric treatment (OR = 68.91). Only in the AOD group the total FSPI scores presented significant correlation with depression, anxiety, and hopelessness. CONCLUSIONS: Individuals with AOD dependence and low scores of family support perception also presented high scores of depression, anxiety, and hopelessness, suggesting that FSPI scores could be a useful 'social marker' of AOD dependence with psychiatric comorbidities. These data also reinforce the relevance of evaluating family support in AOD treatment planning.